Unpacking Cultural Values through Kalasha Proverbs: A Sociolinguistic Study of the Kalash Valleys, Pakistan - Katrina Khan; Kifayat Ullah; Habib Ullah Nawab (Dialogue Social Science Review (DSSR), 2025)
This study explores the rich intangible cultural heritage of the Kalasha people by analysing a selection of their proverbs to uncover their cultural values and wisdom. The research uses qualitative and textual analysis of 30 proverbs, chosen through a purposeful sampling technique from both oral sources and the book Kalasha Matal. As the first study of its kind, it aims to illuminate the cultural significance embedded in Kalasha proverbs. The research is expected to help Kalasha students learn social and cultural values through these meaningful sayings. Furthermore, the study serves as a guide for future generations, presenting Kalasha proverbs in various contexts to educate readers about folklore, cultural history, and linguistics. Ultimately, the goal of this paper is to preserve and promote Kalasha proverbs for future generations.